Ukraine's Many Faces Land, People, and Culture Revisited - Palko, Olena; Férez Gil, Manuel (New Europes, 2023)
Russia's large-scale invasion on the 24th of February 2022 once again made Ukraine the focus of world media. Behind those headlines remain the complex developments in Ukraine's history, national identity, culture and society. Addressing readers from diverse backgrounds, this volume approaches the history of Ukraine and its people through primary sources, from the early modern period to the present. Each document is followed by an essay written by an expert on the period, and a conversational piece touching on the ongoing Russian aggression against Ukraine. In this ground-breaking collection, Ukraine's history is sensitively accounted for by scholars inviting the readers to revisit the country's history and culture. With a foreword by Olesya Khromeychuk.